2012
DOI: 10.3402/ijch.v71i0.18592
|View full text |Cite
|
Sign up to set email alerts
|

Dietary exposure to persistent organic pollutants and metals among Inuit and Chukchi in Russian Arctic Chukotka

Abstract: ObjectivesThe general aim was to assess dietary exposure to selected persistent organic pollutants (POPs) and metals among Eskimo (Inuit) and Chukchi of the Chukotka Peninsula of the Russian Arctic, and to establish recommendations for exposure risk reduction.Study designA cross-sectional evaluation of nutritional patterns of coastal and inland indigenous peoples of the Chukotka Autonomous Okrug (in 2001–2003); assessment of the levels of persistent toxic substances (PTSs) in traditional foods and their compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 8 publications
1
24
0
2
Order By: Relevance
“…The study targeted randomly selected groups of indigenous individuals who were permanent residents of the coastal village of Uelen and the inland village of Kanchalan in the Chukotka Autonomous District (Okrug) in the Far East Region of Russia (for map see [10]). In the 2001 study, 251 residents of Uelen aged between 18 and 71 years were enrolled, of whom 132 were women.…”
Section: Methodsmentioning
confidence: 99%
“…The study targeted randomly selected groups of indigenous individuals who were permanent residents of the coastal village of Uelen and the inland village of Kanchalan in the Chukotka Autonomous District (Okrug) in the Far East Region of Russia (for map see [10]). In the 2001 study, 251 residents of Uelen aged between 18 and 71 years were enrolled, of whom 132 were women.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the PTS study findings, consumption restrictions were recommended for several species and tissues, and several risk communication measures were implemented to reduce contaminant exposure (36). The Ministry of Health Care and Social Development of the Russian Federation approved systematic population health inspections, contaminant waste clean-up projects and training sessions.…”
Section: Russia: Pops and Metals In Chukotkamentioning
confidence: 99%
“…Dudarev (36) reported that the comprehensive study approach in Chukotka and the thorough awareness campaign were very successful in producing desired “outcomes,” that is, implementation exercises and contaminant exposure reduction measures. However, to date there has been no follow-up study to investigate whether the measures taken have caused a desired “impact,” that is, a decrease in contaminant exposure.…”
Section: Russia: Pops and Metals In Chukotkamentioning
confidence: 99%
“…Another study found that the mean PCB level of blubber samples taken from 20 bowhead whales near Barrow, Alaska was 458.5 (ng/g, w/w) (22). A study conducted to assess dietary exposures to POPs and metals in the nearby Chukotka region of the Russian Arctic found that consumption limits were warranted for certain marine and freshwater fish, some muscle tissues of waterfowl and seal, blubber of whale and seal, liver of most animals tested, and kidney tissues of reindeer, walrus, and seal (23). Researchers found elevated levels of PCBs in marine fish near a formerly used military base at Adak Island in the Aleutians that would trigger strict fish consumption advisories according to US EPA risk-based guidance (24).…”
Section: Summaries Of 5 Cbpr Exposure Assessmentsmentioning
confidence: 99%